Serum prolidase and IGF-1 as non-invasive markers of hepatic fibrosis during four different periods after bile-duct ligation in rats - ÇELİKEL, ÇİĞDEM (SPRINGER, 2008)
Aim Our aim was to study the correlation of serum prolidase and insulin like growth factor-1 to liver collagen and assess their utility as markers of fibrosis during four different periods of hepatic injury and fibrosis after bile-duct ligation in rats. Methods Forty-eight Wistar albino rats were included in the study and divided into six groups. Seven rats served as the control group (Control), while seven rats had a sham operation (Sham group). Thirty-four rats underwent bile-duct ligation. Bile-duct ligated (BDL) animals were sacrificed at the end of the first week (Group 1; n = 8), second week (Group 2; n = 8), third week (Group 3; n = 9), or fourth week (Group 4; n = 9) after BDL. Liver collagen, liver prolidase, and serum prolidase and IGF-1, were determined. Results There was a positive correlation between liver collagen and serum prolidase (r(s): 0.843, P < 0.001) levels and a negative correlation among liver collagen and serum IGF-1 levels (r(s): -0.667, P < 0.001). The peak levels of liver collagen and serum prolidase were reached in the third week while the lowest levels of IGF-1 were found at the end of the third week. Conclusion Serum prolidase and IGF-1 either independently or in combination correlate with liver collagen content in hepatic fibrosis.
Keywords: prolidase; IGF-1; collagen; hepatic fibrosis; serum marker; bile-duct ligation; GROWTH-FACTOR-I; LIVER FIBROSIS; PLASMA PROLIDASE; BINDING-PROTEIN; CIRRHOSIS; COLLAGEN; INDEX; HORMONE; DISEASE; PROGRESSION